Analisis Penegakan Hukum Pidana terhadap Kejahatan Korporasi - Riski Yunus; Roy Marthen Moonti; Nurmik K. Martam; Muslim A. Kasim (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Corporate crime within PT Permodalan Nasional Madani (PNM) Palu Branch reflects the vulnerability of state-owned financial institutions to practices of abuse of authority and violation of the law by internal elements. This case caused state losses and damaged public trust. This research aims to analyze the criminal sanctions and obstacles faced by law enforcement officials in cracking down on corporate crime, as well as formulating solutions for handling it. This research uses a normative juridical approach with the support of empirical data from cases in the Palu District Attorney's Office. The results show that criminal sanctions against individual perpetrators have been applied, but have not yet touched on aspects of institutional corporate responsibility. The main obstacles in law enforcement include limited evidence, the complexity of the organizational structure, the apparatus' lack of understanding of corporate law, and external pressures that interfere with the independence of the investigation. Suggestions include the need to increase the capacity of investigators in forensic audit and corporate law, strengthening the internal monitoring and whistleblowing system at PNM, and collaboration between law enforcement agencies. Thus, law enforcement against corporate crime can be carried out more effectively, fairly, and able to prevent the recurrence of similar crimes in the future.